Perencanaan Sumber Daya untuk Pengajaran dan Pembelajaran Bilingual di Sekolah Dasar - Ulya, Nurul Maftuchatul; Mutmainah, Sasa; Prahesthy, Kumala Dwy; Nurisma, Syahrotun Septi; Eriyansari, Manda (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Bilingual education is an approach that is increasingly being implemented in primary schools to meet the challenges of globalization. This article comprehensively discusses resource planning in bilingual learning, covering three main aspects: teachers, students, and facilities and infrastructure. Teachers as the spearhead of education are required to have competence in two languages. Students need to be supported in developing bilingual skills through appropriate curriculum approaches and learning environments. Infrastructure facilities such as learning media, technology and classrooms must also be prepared optimally. With integrated and systematic planning, bilingual education can be implemented effectively and support the development of students’ global competencies.